Предмет: Алгебра,
автор: Dreamw8
Помогите пожалуйста решить уравнение: (x^2+7x+13)^2-(x+3)(x+4)=1
Ответы
Автор ответа:
0
(x²+7x+13)²-(x²+3x+4x+12)=1
(x²+7x+13)²-(x²+7x+12)=1
(x²+7x+13)²-(x²+7x+13)+1=1
(x²+7x+13)²-(x²+7x+13)=0 пусть х²+7x+13=t
t²-t=0 t(t-1)=0 t=0 t=1
1) x²+7x+13=0 или 2)х²+7х+13=1
D=7²-4*1*13=49-52=-3 -нет корней
2) D=7²-4*12=49-48=1 x1=-7+1/2=-6/2=-3 x2=-7-1/2=-8/2=-4
(x²+7x+13)²-(x²+7x+12)=1
(x²+7x+13)²-(x²+7x+13)+1=1
(x²+7x+13)²-(x²+7x+13)=0 пусть х²+7x+13=t
t²-t=0 t(t-1)=0 t=0 t=1
1) x²+7x+13=0 или 2)х²+7х+13=1
D=7²-4*1*13=49-52=-3 -нет корней
2) D=7²-4*12=49-48=1 x1=-7+1/2=-6/2=-3 x2=-7-1/2=-8/2=-4
Похожие вопросы
Предмет: Другие предметы,
автор: evgenialove52
Предмет: Английский язык,
автор: juju8kms
Предмет: Английский язык,
автор: kosta939
Предмет: Математика,
автор: zollo23